The influence of ionic liquid pretreatment on the physicomechanical properties of polymer biocomposites: A mini-review - Shamsuri Ahmad Adlie; Jamil Siti Nurul Ain Md.; Abdan Khalina (e-Polymers, 2022)
Increasing concern for the environment has led researchers to pay more attention to the fabrication of polymer biocomposites for many different applications. Polymer biocomposites have generally been fabricated utilizing synthetic or natural polymers with natural fillers. Recently, ionic liquids have been used for the pretreatment of natural fillers prior to the fabrication of polymer biocomposites. In this mini-review, four types of ionic liquids used for the pretreatment of natural filler are classified, specifically chloride-, diethyl phosphate-, acetate-, and bistriflimide-based ionic liquids. In addition, the pretreatment processes of natural fillers with ionic liquids are described in this review. Furthermore, the influence of ionic liquid pretreatment on the physicomechanical properties of polymer biocomposites is succinctly reviewed. Besides, the information presented in this review contributes to a clearer understanding of the process of ionic liquid pretreatment and the vital physicomechanical properties of polymer biocomposites. In summary, most ionic liquid pretreatments can improve almost all physicomechanical properties of polymer biocomposites.